PERBANDINGAN KEMAMPUAN LABA AGREGAT DAN LABA DISAGREGAT DALAM MEMPREDIKSI ARUS KAS OPERASI SATU TAHUN MENDATANG DAN RETURN SAHAM (Studi empiris pada perusahaan-perusahaan manufaktur yang terdaftar di BEI periode 2008 s.d. 2011) - Vina Firdausia Khalida; Anis Chariri (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of aggregate earnings and disaggregate earnings to operating cash flow next year and stock returns. In addition, this study also examines whether disaggregate earnings have a better ability to predict operating cash flow and return the next year than aggregate earnings.The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) of the years 2008-2011. Samples in this study were drawn through purposive sampling. Operating cash flow next year and stock returns predicted using disaggregate earnings consisting of operating cash flow and total accruals using multiple regression.The results of this study indicate that the operating cash flow next year can be predicted using aggregate earnings and disaggregate earnings. In addition, disaggregate earnings consisting of operating cash flow and total accruals improve the predictive ability of aggregate earnings. However, aggregate earnings and disaggregate earnings don’t have the ability to predict stock returns